27‐1: Invited Paper: Performance Benchmarking of Wide Color Gamut Televisions and Monitors. Issue 1 (May 2016) - Sadasivan, Sridhar; Bausemer, Katherine; Corliss, Steven; Pratt, Robert
Abstract : Wide color gamut displays on the market were studied. TVs displaying over 90% NTSC gamut area and monitors displaying over 100% Adobe coverage were selected. CdSe QD based solutions achieve the highest color and energy efficiency, which is linked to fundamental attributes of QDs: narrow emission, efficiency, and operational stability.